Is Salvage Autologous Stem Cell Transplantation Still a Viable Treatment Option in Relapsed Myeloma Patients? - Luka Čemažar; Matevž Škerget; Barbara Skopec (Medicina)
Background and Objectives: The role of salvage autologous stem cell transplantation (SAT) in relapsed multiple myeloma (MM) has been increasingly questioned, particularly with the emergence of novel immunotherapies and cellular therapies. This study aimed to evaluate the efficacy of SAT in a cohort of patients with relapsed MM following their first autologous stem cell transplantation (ASCT). Materials and Methods: A retrospective analysis was conducted on 78 patients from our institutional registry who underwent SAT for relapsed MM between April 2008 and October 2023. The primary endpoint was the progression-free survival (PFS), with secondary endpoints including the overall survival (OS) and overall response rates (ORRs) on day +100 after SAT. Results: The median age of the patients was 62 years (range: 48–78), and 32% were female. Most patients (81%) received reinduction therapy before SAT. The median PFS and OS from SAT were 24 months (95% CI: 20–36) and 76 months (95% CI: 48-NR), respectively. The ORR was 85%, and 65% achieved at least a very good partial response (VGPR). No significant differences in the PFS were found between subgroups based on the maintenance following SAT (hazard ratio (HR) = 0.93, 95% CI: 0.48–1.8, p = 0.831), cytogenetic risk (standard vs. high-risk) (HR = 0.98, 95% CI: 0.49–1.99, p = 0.969), age (<60 years vs. ≥60 years) (HR = 0.96, 95% CI: 0.5–1.85, p = 0.912) or number of prior treatment lines (<3 vs. ≥3) (HR = 0.186, 95% CI: 0.95–3.61, p = 0.069). The duration of remission after the first ASCT did not influence the PFS or OS following SAT (HR = 1.63, 95% CI: 0.78–3.39, p = 0.193 and HR = 1.2, 95% CI: 0.46–3.09, p = 0.7130). Conclusions: Salvage autologous stem cell transplantation remains a viable treatment option for patients with relapsed MM, particularly in resource-limited countries or for patients who prefer short, fixed-duration therapy. However, as is known from previous studies, maintenance therapy is crucial for achieving longer PFS. In this study, no statistically significant factors were identified to predict the benefit, underscoring the need for further research to optimize patient selection.